Selective targeting of non-centrosomal AURKA functions through use of a targeted protein degradation tool - Richard Wang (Nature Portfolio, 2021)
Wang et al develop tools to target the mitotic regulator AURKA by synthesising PROTACs based on the inhibitor MLN8237. They find that the new PROTAC compound efficiently clears cytoplasmic and mitotic spindle-associated AURKA but does not eliminate AURKA activity from centrosomes, demonstrating the possibility of targeting subpopulations.